Construction and Characterization of Coated Wire Oxalate Ion Selective Electrode Based on Chitosan - Zuri Rismiarti; Atikah Atikah; Hermin Sulistyarti (Chemistry Department, The University of Brawijaya, 2014)
PVC (polyvinyl chloride) membrane based coated wire oxalate ion selective electrode has been developed by using chitosan. The results showed the optimum composition of the membrane was chitosan: aliquat 336: PVC: DBP = 4:1:33:62 (% weight). The electrode showed Nernstian response, Nernst factor 29.90 mV/decade of concentration, linier concentration range of 1x10-5 - 1x10-1 M, detection limit of 2.56 x10-6 M, response time of 30 second, and life time of 42 days. ISE’s performance worked well in pH range of 5-7 and temperature of 25-50 oC. Validation test showed no significant difference (t test) with the SSA method so that the potentiometric method could be used as an alternative method for determining urinary oxalate.